Persepsi guru tentang pelayanan tenaga administrasi sekolah di sekolah menengah atas - Suhada, Yolla Rahma; Santoso, Yulianto (Deduksi: Jurnal Dedikasi Edukasi, 2023)
The purpose of this study was to obtain information about the services of School Administrative Personnel at State High Schools (SMA) in Pauh District, consisting of SMA N 9 Padang and SMA N 15 Padang. This research question is how good the teacher's perception is of the service of School Administrative Staff in terms of (1) friendliness (2) responsibility (3) comfort (4) speed of service. This type of research uses Descriptive Quantitative with the population in this study being Civil Servant (PNS) teachers with a population of 87 people and a sample of 54 people. Sampling is determined by the Slovin formula at an error rate of 10% and taken using the Stratified Proportional Random Sampling Technique. The research instrument used was in the form of a questionnaire in the form of a Likert scale. Before the questionnaire was used, it was first tested to determine the validity and reliability using SPSS version 23 assistance and obtained validity test results, namely from 40 statement items there were 38 valid items and 2 invalid items (void) and the reliability test results with N = 20 at a 90% confidence level were 0.444. So we get a calculation of > rtable (0.955>0.444). The results of the data analysis showed that the service of School Administration Personnel in the State High School (SMA) of Pauh District was fairly good with an achievement level of 4.47 with the following explanation; (1) friendliness in the good category, namely in the achievement of 4.43 (2) responsibility in the good category, namely in the achievement of 4.43, (3) comfort in the good category, namely in the achievement of 4.53, (4) Speed of service in the good category, which is in the achievement of 4.51.